2017
DOI: 10.1002/jeab.280
|View full text |Cite
|
Sign up to set email alerts
|

Dogs don't always prefer their owners and can quickly form strong preferences for certain strangers over others.

Abstract: The unique relationship between dog and owner has been demonstrated in several experimental procedures, including tests in which dogs are left alone or with a stranger, tests of dogs' appeasement or social approach when petted by their owner or a stranger, and their ability to learn when taught by their owner or a stranger. In all cases, dogs responded differently to their owner, which has been referred to as a specific attachment, and likely a product of a prolonged history of reinforcement. In the current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Results from individual procedures in the current experiment replicated those of previous studies assessing human attention as a reinforcer for dog behavior. Previous studies that have utilized the concurrent-operant procedure have found that dogs will allocate some of their time to the person providing attention, even when the alternative is food (Feuerbacher & Wynne, 2014, 2015, 2017). While some dogs in the current experiment demonstrated a larger disparity between time spent within proximity of the assistant providing attention and time spent within proximity of the assistant providing no programmed consequence, all dogs allocated more of their time to the assistant providing attention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from individual procedures in the current experiment replicated those of previous studies assessing human attention as a reinforcer for dog behavior. Previous studies that have utilized the concurrent-operant procedure have found that dogs will allocate some of their time to the person providing attention, even when the alternative is food (Feuerbacher & Wynne, 2014, 2015, 2017). While some dogs in the current experiment demonstrated a larger disparity between time spent within proximity of the assistant providing attention and time spent within proximity of the assistant providing no programmed consequence, all dogs allocated more of their time to the assistant providing attention.…”
Section: Resultsmentioning
confidence: 99%
“…Approach behaviors are often followed by human attention, which means that for the behavior to continue, human attention would need to function as a reinforcer. Several researchers have previously looked at the reinforcing efficacy of human attention on shelter animal behavior (e.g., Feuerbacher & Wynne, 2012, 2014, 2015, 2017). However, equivocal results, potentially due to procedural differences from these studies, have left it unclear as to whether or what type of human attention is reinforcing (i.e., vocal or physical).…”
mentioning
confidence: 99%
“…Familiarity can influence interactions between humans and other mammals, including those kept on farms [1], in zoos [2], in research settings [3], and as companion animals [4]. For instance, handled piglets (Sus scrofa) interacted longer with their handler than with a stranger and showed less agitation and avoidance when caught by their handler [5].…”
Section: Introductionmentioning
confidence: 99%
“…As a result of a shared transition to increased tolerance/friendliness, humans and dogs both show:-tendencies to seek out novelty(Gácsi et al 2005;Miklosi 2014) -abilities to follow subtle gestural and emotional clues(Hare and Tomasello 2005) -hypersociability, e.g. infants motivated to explore new relationships with strangers(Shuldiner et al 2017;Feuerbacher and Wynne 2017), and there are similar genetic underpinnings to human and dog hypersociability(vonHoldt et al 2017) -a period of socialisation in infancy, which guides orientations and expectations towards others in adulthood(Miklosi 2014) -sensitivity/vulnerability to a lack of social support and emotional connection(Miklosi 2014) -a tendency to look for help from others to solve problems(Miklósi et al 2003;Gácsi et al 2005) -abilities to have a dual identity -relating in one way to one species and in different ways to another(Bradshaw 2017), including abilities to relate to humans/dogs as alternative attachment figures (Kis et al 2014; Nagasawa et al 2015; Thielke and Udell 2017) -tendencies to seek compensatory attachments in objects (dogs can also have attachment objects) (unpublished survey, University of Bristol Veterinary school)…”
mentioning
confidence: 99%